Experimental studies on the instantaneous fluid–structure interaction of an air-inflated flexible membrane in turbulent flow. (July 2018) - Wood, J.N.; Breuer, M.; De Nayer, G.
Abstract: The present paper investigates the interaction between a turbulent fluid flow and a flexible membrane structure. Such flexible structures are of increasing interest for modern engineering applications due to their adaptable utilization. Highly flexible membranes under turbulent flow conditions still bare fundamental challenges such as the structural response to fluid loads leading to the motivation of the present study. It investigates the fluid–structure interaction of a flexible membranous structure in the shape of a hemisphere. The air-inflated structure is placed in the test section of a wind tunnel and is exposed to a turbulent boundary layer flow. The properties of the turbulent boundary layer are clearly defined so that the test case is reproducible by numerical simulations. Three Reynolds numbers (50, 000, 75, 000 and 100, 000) are chosen to examine the interaction between the turbulent flow and the pressurized membrane. Special emphasis is put on the instantaneous effects. Furthermore, the flow field around an equally sized rigid hemisphere is measured under identical conditions serving as a reference for the flexible case. The experiments are conducted by combining particle-image-velocimetry for the flow field and high-speed digital-image correlation measurements for the deformation of the oscillating membrane. Furthermore, a constant-temperature anemometer is used for evaluating the velocity spectra at locations close to the wall to connect the independently performed fluid and structure measurements. A thorough analysis of the comprehensive data sets for the fluid flow and the displacements of the structure leads to the characterization of the behavior of the flexible structure under changing flow conditions.